THE INFLUENCE OF TOUR GUIDES ON THE PROGRESS OF TOURISM IN WEST SUMATRA - Novra, Eddi; Diana, Winda; Abdi, Moch (Ensiklopedia of Journal, 2025)
West Sumatra is a prominent tourist destination in Indonesia, known for its rich cultural heritage and natural beauty. This study investigates the role of tour guides in enhancing tourist satisfaction and advancing tourism development in the region. A mixed-methods approach was employed, involving surveys with 200 tourists and interviews with 20 professional tour guides. The results indicate high tourist satisfaction levels, with 91% expressing overall satisfaction and 89% appreciating the quality of cultural information. However, challenges such as language barriers, lack of training, and limited technological access were identified as significant issues faced by tour guides. Key tourism indicators, including tourist arrivals, hotel occupancy rates, and average stay durations, showed steady growth from 2021 to 2024, highlighting the positive impact of tour guide services. The study underscores the need for targeted professional development, improved promotional strategies, and technological integration to address these challenges and sustain tourism growth. Recommendations for future research and practical strategies to enhance the role of tour guides are provided. Keywords: Tourist Satisfaction, Tour Guides, Tourism Development, Cultural Heritage, West Sumatra